Legal position and living conditions of peasants and commoners in early medieval Ireland, c.680 - c.1170 - Peters, Cherie N. (Trinity College (Dublin, Ireland). Department of History, 2014)
This thesis discusses the non-noble classes of early medieval Ireland under the categories of 'commoner' - a hereditary landowning freeman of non-noble status, most typically termed in Irish bóaire; 'peasant' - a semi-free tenant-at-will, most commonly termed in Irish fuidir (also bothach); and 'serf - a semi-free cultivator bound to the soil, most commonly termed in Irish senchléithe. All three of these status-groups are often subsumed in the historiography of the early middle ages under the polysemous term 'peasantry'.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin